Cross-national differences in adolescents’ sleep patterns: a time-use approach - Joan Garcia-Roman; Pablo Gracia; Giulia Zerbini (International Journal of Adolescence and Youth)
Good sleep contributes to health and performance. However, insufficient and poor sleep are very common among adolescents today. This study examines cross-national differences in adolescents’ sleep and activity patterns across Finland, France, Hungary, Italy, Netherlands, South Africa, South Korea, Spain, and the UK, using an innovative 24-hour time-use approach with time-diary data (N = 25,248 diaries; mean age 15.4 years; 50.3% girls). Sleep duration ranges from 7:21 hours (South Korea) to 8:46 hours (South Africa, UK) on schooldays and from 9:13 hours (South Korea) to 10:33 hours (Netherlands) on non-schooldays. South Africa shows the earliest and Spain the latest sleep onsets and wake-up-times. Insufficient sleep duration (i.e. less than 8 hours) ranges from 19% (South Africa) to 69% (South Korea) on schooldays. Activity patterns before sleep (e.g. eating, screen time, studying) also differ strongly across countries. Our findings could support policy makers in developing effective strategies to improve adolescent sleep.